Competencies of Career-Entry Medical Technology Graduates of Lyceum of Batangas: Basis for Enhancement of the Internship Training Program - Valdez, Anacleta P. (JPAIR Multidisciplinary Research, 2010)
The role of medical technologists in the clinical laboratory has changed within the last five years due to changes in the laboratory environment. Substantial modification in the medical technology curriculum is needed to prepare graduates for technologic, regulatory, staffing and operational changes in laboratory medicine. It is the ultimate goal of the College to prepare students for career entry positions as medical technology professionals. The curriculum should be designed to prepare the graduates and demonstrate the core competencies expected of them in the workplace. It is for this reason that this study was conducted to assess the career entry level competencies expected of the graduates of the College of Medical Technology of Lyceum of Batangas. Findings of the study served as basis in enhancing the curriculum to make it more responsive to the needs of local and international healthcare systems. Using a descriptive method, the respondents were the chief medical technologists and immediate supervisors of selected hospitals who have as their staff LB Medical Technology graduates under the AHSE curriculum (2002-2006). A total of 77/138 (56%) graduates were evaluated using a structured type of questionnaire following a Likert scale with 5 as the highest and one as the lowest values. The parameters in the questionnaire were derived from the model formulated from the various competency-based standards of various local and international accrediting professional associations.
Keywords: Competency; medical technology; LPU- Batangas